(4x-2)+(2x+14)=5x+10

Simple and best practice solution for (4x-2)+(2x+14)=5x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-2)+(2x+14)=5x+10 equation:


Simplifying
(4x + -2) + (2x + 14) = 5x + 10

Reorder the terms:
(-2 + 4x) + (2x + 14) = 5x + 10

Remove parenthesis around (-2 + 4x)
-2 + 4x + (2x + 14) = 5x + 10

Reorder the terms:
-2 + 4x + (14 + 2x) = 5x + 10

Remove parenthesis around (14 + 2x)
-2 + 4x + 14 + 2x = 5x + 10

Reorder the terms:
-2 + 14 + 4x + 2x = 5x + 10

Combine like terms: -2 + 14 = 12
12 + 4x + 2x = 5x + 10

Combine like terms: 4x + 2x = 6x
12 + 6x = 5x + 10

Reorder the terms:
12 + 6x = 10 + 5x

Solving
12 + 6x = 10 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
12 + 6x + -5x = 10 + 5x + -5x

Combine like terms: 6x + -5x = 1x
12 + 1x = 10 + 5x + -5x

Combine like terms: 5x + -5x = 0
12 + 1x = 10 + 0
12 + 1x = 10

Add '-12' to each side of the equation.
12 + -12 + 1x = 10 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 10 + -12
1x = 10 + -12

Combine like terms: 10 + -12 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| 5h-(1.5h+4)=10 | | 8=-.5x=21/2 | | bx+6=dx+3*x | | Y+m=6x+20 | | -33=-3f | | -1/2x=16=36 | | 9n+2n-4n=100-(-3)-40 | | 6(m+2)=18+3(m+5) | | 1.19x=.36x+3.6 | | 2(12x+6)+19= | | -5-(t/5)-9 | | 36=-1/2x=16 | | 26+6x+20=46+10x | | 4y-7=y+1 | | 2/7(x-9)=-5 | | .01x=-.01 | | 21+7w=12+6w | | 5*n=3000 | | 16x-1/2=36 | | s+5=6+2 | | y/n-3=11 | | x/.3=-.8 | | 5*2=9*5 | | 1.33x=7 | | b^2+8b-70=0 | | 89/3 | | 4x+8=4x+24 | | 1.43x=x+3 | | (7x-2)-(2x+8)=3x+14 | | 45*75-76x(y+45)-76= | | 1+(-2x)+5=4x+(-3) | | 7t^2-6=0 |

Equations solver categories